CD160 Promotes NK Cell Functions by Upregulating Glucose Metabolism and Negatively Correlates With HIV Disease Progression - Sun, Zheng; Li, Yidi; Zhang, Zining; Fu, Yajing; Han, Xiaoxu; Hu, Qinghai; Ding, Haibo; Shang, Hong; Jiang, Yongjun (Frontiers in Immunology, 2022)
Natural killer (NK) cells are crucial for immune responses to viral infections. CD160 is an important NK cell activating receptor, with unknown function in HIV infection. Here, we found that CD160 expression was reduced on NK cells from HIV-infected individuals and its expression was negatively correlated with HIV disease progression. Further, GLUT1 expression and glucose uptake were higher in CD160+ NK cells, and the results of RNA-seq and flow cytometry demonstrated that CD160 positively regulated glucose metabolism through the PI3K/AKT/mTOR/s6k signaling pathway, thereby enhancing NK cell function. Moreover, we determined that reduced CD160 expression on NK cells could be attributed to the higher plasma levels of TGF-β1 in HIV-infected individuals. Overall, these results highlight the vital role of CD160 in HIV disease progression and regulation of glucose metabolism, indicating a potential target for HIV immunotherapy.